Kiprah Agama Melawan Terorisme - Frederikus Fios (Humaniora, 2011)
Religion and terrorism are the two (2) terms that go hand in hand with each other throughout the history of our humanity. Religion and terrorism became a classic story that characterizes the dynamics of human history from time to time. Safe and peaceful situation was far from our social reality. It should not be allowed. Need to be reconstructed in ways and surefire strategies to restore the condition of Indonesian people towards good and true. It takes a critical awareness of the depth of every religion in Indonesia to be inclusive towards others of other faiths. It is worth noting that terrorism is often the name of religion as an ideology behind the movement.